Self-assembled liposome-loaded microbubbles: the missing link for safe and efficient ultrasound triggered drug-delivery - Geers, Bart; Lentacker, Ine; Sanders, Niek N.; Demeester, Joseph; Meairs, Stephen; De Smedt, Stefaan C. (Journal of controlled release, 2011)
Liposome-loaded microbubbles have been recently introduced as a promising drug delivery platform for ultrasound guided drug delivery. In this paper we design liposome-loaded (lipid-shelled) microbubbles through the simple self-assembly of the involved compounds in a single step process. We thoroughly characterized the liposome-loading of the microbubbles and evaluated the cell killing efficiency of this material using doxorubicin (DOX) as a model drug. Importantly, we observed that the DOX liposome-loaded microbubbles allowed killing of melanoma cells even at very low doses of DOX. These findings clearly prove the potential of liposome-loaded microbubbles for ultrasound targeted drug delivery to cancer tissues.
Gesehen am 28.09.2023